Using magnetic mesoporous silica nanoparticles armed with EpCAM aptamer as an efficient platform for specific delivery of 5-fluorouracil to colorectal cancer cells - Kamil Mohammad Al-Mosawi, Aseel; Bahrami, Ahmad Reza; Nekooei, Sirous; Saljooghi, Amir Sh.; Matin, Maryam M. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Theranostic nanoparticles with both imaging and therapeutic capacities are highly prom-ising in successful diagnosis and treatment of advanced cancers. Methods: Here, we developed mag-netic mesoporous silica nanoparticles (MSNs) loaded with 5-fluorouracil (5-FU) and surface-decorated with polyethylene glycol (PEG), and epithelial cell adhesion molecule (EpCAM) aptamer (Apt) for controlled release of 5-FU and targeted treatment of colorectal cancer (CRC) both in vitro and in vivo. In this system, Au NPs are conjugated onto the exterior surface of MSNs as a gatekeeper for intelligent release of the anti-cancer drug at acidic conditions. Results: Nanocarriers were prepared with a final size diameter of 78 nm, the surface area and pore size of SPION-MSNs were calculated as 636 m2g−1, and 3 nm based on the BET analysis. The release of 5-FU from nanocarriers was pH-dependent, with an initial rapid release (within 6 h) followed by a sustained release for 96 h at pH 5.4. Tracking the cellular uptake by flow cytometry technique illustrated more efficient and higher uptake of targeted nanocarriers in HT-29 cells compared with non-targeted formula. In vitro results demon-strated that nanocarriers inhibited the growth of cancer cells via apoptosis induction. Furthermore, the targeted NPs could significantly reduce tumor growth in immunocompromised C57BL/6 mice bearing HT-29 tumors, similar to those injected with free 5-FU, while inducing less side effects. Conclusion: These findings suggest that application of Apt-PEG-Au-NPs@5-FU represents a promising theranostic platform for EpCAM-positive CRC cells, although further experiments are required before it can be practiced in the clinic.